Association study and expression analysis of CD9 as candidate gene for boar sperm quality and fertility traits - Kanokwan Kaewmala (2018)
Cluster-of-differentiation antigen 9 (CD9) gene expressed in the male germ line stem cells is crucial for sperm-egg fusion, and was therefore selected as candidate gene for boar semen quality. The association of CD9 with boar sperm quality and fertility trait was analyzed using a total of 340 boars both from purebred Pietrain and Pietrain×Hampshire crosses. A single nucleotide polymorphism (g.358A>T) in intron 6 was significantly associated with sperm motility (MOT) (P<0.001), plasma droplet rate (PDR) (P<0.001) and abnormal spermatozoa rate (ASR) (P<0.01). Boars were divided into two groups with group 1 (G-I) boars having a higher SCON and SMOT, lower SVOL (sperm volume) and group 2 (G-II) having a lower SCON and SMOT, higher SVOL. The mRNA and protein expression levels were evaluated in reproductive, non-reproductive tissues and spermatozoa from G-I and G-II animals by using quantitative real-time PCR and western blotting. When both reproductive and non-reproductive tissues were examined, highest mRNA was expressed in prostate gland, then in the body of the epididymis, vas deferens and tail of the epididymis. In case of reproductive tissues, CD9 expression was higher in tissues and spermatozoa collected from G-I boars than those collected from G-II boars. The mRNA expression was significantly different (P<0.05) in body of epididymis from G-I and G-II boars. The CD9 protein expression results from western blot were coincided with the results of qRT-PCR. Moreover, CD9 protein localization in Leydig cells, Sertoli cells, epithelial cells and spermatozoa was remarkable which indicated the important role of CD9 in spermatogenesis process. By using mRNA and protein expression profiles, it could be shown that CD9 plays a crucial role during sperm development, especially within the epididymis where the maturation of the sperm, a key process for the sperm quality and motility takes place. These results will improve the understanding of the functions of the CD9 in spermatogenesis within the reproductive tracts and will shed light on CD9 as a candidate gene in the selection of good sperm quality boars. © 2011 Elsevier B.V.